Public use of the Internet at Chester library, UK. - Katherine Turner; Margaret Kendall (Information Research: An International Electronic Journal, 2000)
Substantial investment is accelerating the provision of public access to the Internet in UK public libraries. Monitoring and evaluation will be essential to inform policies, developments and justify the new services. This paper reports on quantitative and qualitative research into the use being made of the Internet facilities at Chester Library between August 1998 and May 1999. A questionnaire survey of 178 users revealed substantial use by non-library members, mostly aged between 16 and 35, with only slightly higher use by men than by women. Most of the sample had received no formal training in Internet use and the most popular application was e-mail. Follow-up interviews with 9 users provide examples of the value of the service to users and recommendations for increased training and support from librarians. Analysis of the results includes recommendations for Chester libraries and contributes to the wider debate on the changing roles of public libraries. Further research on the monitoring and evaluation of IT-based services in public libraries is now underway at Manchester Metropolitan University, with Cheshire libraries being one of three library authority project partners in VITAL, an 18 month study funded by the Library and Information Commission.